Policy and financial consultancy services : rice industry study prepared for the CARICOM Secretariat (The Company HoletownUS, 2005)
Examines constraints in the rice industry of Guyana and looks at investment in the industry. Notes the impact of intervention and suggests some innovative financial approaches. Outlines the proposed development startegy for achieving the recommendations made in the report.
Keywords: RICE